Absolute cardiovascular disease risk score and pharmacotherapy at the time of admission in patients presenting with acute coronary syndrome due to coronary artery disease in a single Australian tertiary centre: a cross-sectional study. Issue 2 (8th February 2021) - Bailey, Amy; Korda, Rosemary; Agostino, Jason; Stanton, Tony; Kelly, Gabriela; Richman, Tuppence; Greaves, K
Abstract : Objectives: To describe (1) absolute cardiovascular disease risk (ACVDR) scores in patients presenting to hospital with acute coronary syndrome (ACS) and (2) proportions of these patients on guideline-recommended pharmacotherapy according to their ACVDR score. Design: Cross-sectional study. Setting: Single-site tertiary centre hospital, Queensland, Australia over a 12-month period. Participants: Patients >18 years of age presenting to hospital with ACS due to coronary artery disease (CAD) confirmed by angiography. Primary and secondary outcome measures: Proportion of patients without prior history of CVD with a high ACVDR score, and of patients with a prior history of CVD, who are on guideline-recommended pharmacotherapy. Results: 527 ACS patients were included of whom the mean age was 63 years and 75% were male. Overall, 66% (350) had no prior CVD and 34% (177) patients had prior CVD. In patients with no prior CVD, the proportions of patients with low, intermediate and high CVD risk scores were 41%, 24% and 36%. In the no prior CVD, high-risk patient group, 48% were on no preventative pharmacotherapy, 32% on single pharmacotherapy and 20% patients on complete guideline-recommended pharmacotherapy. In the prior CVD group, 7% patients were on no pharmacotherapy, 40% on incomplete pharmacotherapy and 53% were on complete guideline-recommended pharmacotherapy. Conclusion: This study adds to the evidence on implementation gaps in guideline-recommended management of ACVDR, showing that a large proportion of patients presenting with ACS due to CAD were at high risk of developing CVD prior to the event and most were not on guideline-recommended treatment. A significant proportion of these events are likely to have been preventable, and therefore, increased assessment and appropriate treatment of ACVDR in primary care is needed to reduce the incidence of CVD events in the population.